Scattering characteristics of two-dimensionally periodic impedance surface. - Ruey Bing Hwang (IEEE Transactions on antennas and propagation)
We present an exact formulation for the three-dimensional (3-D) boundary-value problem of plane wave scattering by a two-dimensionally (2-D) periodic impedance surface in a uniform medium. The scattering characteristics of such a structure are rigorously analyzed in terms of the complete set of both TE- and TM-polarized plane waves in the uniform medium. Extensive numerical results are given to illustrate physical phenomena associated with the structure